2007
DOI: 10.1089/end.2006.0222
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Retroperitoneoscopic Partial Adrenalectomy for Large Adrenocortical Oncocytoma

Abstract: A young woman had mild hypertension, and on evaluation, a large tumor arising from the right adrenal gland was found. The tumor was hormonally inactive. Retroperitoneoscopic partial adrenalectomy was carried out. The histopathology report described adrenocortical oncocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Partial adrenalectomy is proposed in some case, however it is an incomplete approach to incidentally detected adrenal mass [94] .…”
Section: Therapymentioning
confidence: 99%
“…Partial adrenalectomy is proposed in some case, however it is an incomplete approach to incidentally detected adrenal mass [94] .…”
Section: Therapymentioning
confidence: 99%
“…In terms of location, AONs were found to have a slight prevalence on the left side (L/R: 1.4/1), which was lower than previously reported in the literature (L/R 3.5/1) [7]. In nine cases, the origin was ectopic, with four occurring in the retroperitoneal region [16,17,[19][20][21], and the others located at the posteroinferior region of the cecum [3], hepatic [14], renal [15], and lumbar spine [18].…”
Section: Discussionmentioning
confidence: 59%
“…AON patients presented a mean age at diagnosis of 44.2 years (range 3.5-87 years) and a female-tomale ratio of 1.9/1. AONs occurred with a slight prevalence on the left side (L/R: 1.4/1); in three cases (1.2%), they were bilateral [11][12][13], and in nine, the origin was ectopic [3,[14][15][16][17][18][19][20][21]. The masses had an average diameter of 8.9 cm (range 2-28 cm) and an average weight of 467 g (range 8-5720 g) [22,23].…”
Section: Resultsmentioning
confidence: 98%
“…In the literature, there are many reports of laparoscopic excision of adrenocortical oncocytomas; however, there are only five reports of laparoscopic excision of an adrenocortical oncocytoma ( Table 2). Modi et al reported the first partial laparoscopic adrenalectomy for retroperitoneal excision of a large adrenal oncocytoma in a young woman with mild hypertension in 2007 [8]. Subsequently, Tian et al reported retroperitoneal laparoscopic excision of an oncocytoma of the adrenal gland of a 37-year-old woman with no history of hypertension [9].…”
Section: Discussionmentioning
confidence: 99%